Limited Neonatal Carbohydrate-Specific Antibody Repertoire Consecutive to Partial Prenatal Transfer of Maternal Antibodies - Kappler, Katharina; Restin, Tanja; Lasanajak, Yi; Smith, David F.; Bassler, Dirk; Hennet, Thierry (Frontiers in Immunology, 2020)
Despite the prominence of carbohydrate-specific antibodies in human sera, data on their emergence and antigen specificities are limited. Whereas maternal IgG are transferred prenatally to the fetal circulation, IgM present in cord blood originate from fetal B lymphocytes. Considering the limited exposure of the fetus to foreign antigens, we assessed the repertoire of carbohydrate-specific antibodies in human cord blood and matched maternal blood samples using glycan arrays. Carbohydrate-specific IgM was absent in cord blood, whereas low cord blood IgG reactivity to glycans was detectable. Comparing IgG reactivities of matched pairs, we observed a general lack of correlation in the antigen specificity of IgG from cord blood and maternal blood due to a selective exclusion of most carbohydrate-specific IgG from maternofetal transfer. Given the importance of intestinal bacteria in inducing carbohydrate-specific antibodies, we analyzed global antibody specificities towards commensal bacteria. Similar IgG reactivities to specific Bacteroides species were detected in matched cord and maternal blood samples, thus pointing to an efficient maternal transfer of anti-microbial IgG. Due to the observed selectivity in maternofetal IgG transfer, the lack of fetal antibodies to carbohydrate epitopes is only partially compensated by maternal IgG, thus resulting in a weak response to carbohydrate antigens in neonates.